Streamlined Iterative Assembly of Thio‐Oligosaccharides by Aqueous S‐Glycosylation of Diverse Deoxythio Sugars. Issue 3 (10th January 2022) - Wen, Peng; Jia, Peijing; Fan, Qiuhua; McCarty, Bethany J.; Tang, Weiping
Abstract: A streamlined iterative assembly of thio‐oligosaccharides was developed by aqueous glycosylation. Facile syntheses of various deoxythio sugars with the sulfur on different positions from commercially available starting materials were described. These syntheses featured efficient chemical methods including our recently reported BTM‐catalyzed site‐selective acylation. The resulting deoxythio sugars could then be used for the Ca(OH)2 ‐promoted protecting group‐free S ‐glycosylation in water at room temperature. The aqueous glycosylation reaction proceeded smoothly to afford the corresponding 1, 2‐ trans S ‐glycosides in good yields with high chemo‐ and stereoselectivity. An appropriate choice of protecting groups for the thiol in the glycosyl donor was necessary for the development of iterative synthesis of thio‐oligosaccharides. The aqueous glycosylation was then applied to the synthesis of a trimannoside moiety of N ‐linked glycans core region. Abstract : Step by step : A streamlined practical iterative synthesis of S ‐oligosaccharides is developed in aqueous solution without the need of protecting any of the hydroxy groups. Various deoxythio sugar building blocks can be prepared efficiently. The Ca(OH)2 ‐promoted aqueous S ‐glycosylation can be realized with high chemo‐ and stereoselectivity.